Post-crisis changes in employment and educational structure of the labor force in Bulgaria - Elka Syarova (Journal of Contemporary Economic and Business Issues, 2015)
The report explores the main impact of the crisis on the Bulgarian labor market whereby the key points are focused on the relation between changes in employment and educational structure of the labor force in Bulgaria, which took place under the influence of the crisis, and the trends of their variation in the post-crisis period. By means of the methods and instruments of the theoretical and descriptive analysis it is proved that crisis development affects to a specific extent the groups involved in different levels of education. Special role for this is attributed to the existing industrial structure and business organization in the country. Certain arguments lead to the conclusion and expectation of a relatively slow recovery of the Bulgarian economy in view of the noticeable trends in the educational structure of employment in the period following the drop in 2009. By applying the means of comparative analysis, we can point out certain similarities and differences with the trends being developed in other European countries in terms of the post-crisis employment of various educational groups of the labor force.
Keywords: O40; J01; J21; J23; J64; 330; economic crisis; labor market; employment; educational structure of the laborforce